The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.24018/ejmed.2020.2.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Exposure to Domestic Violence, Depression and Cyberbullying Among Secondary School Adolescents

Abstract: Literatures on high prevalence of domestic violence are well documented. There is however paucity of research on exposure to domestic violence relates to cyber bullying behavior among Nigerian adolescents. The focus of this study was to determine the correlation between Exposure to Domestic Violence (EDV), depression and cyber bullying behavior among secondary school adolescents. A total of 300 purposively selected secondary school adolescents in Oshodi Isolo, Lagos metropolis Nigeria responded to Child Exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Research has suggested that understanding psychosocial processes is the best way to explain unethical behavior among youth Lee et al, 2022). Various forms of youth interpersonal violence, such as victimization and delinquency, have been linked in studies with lower levels of self-control, resilience and different forms of domestic violence (Akpunne et al, 2020;Jones & Pierce, 2021). Adults who are exposed to domestic violence during their childhood are susceptible to engaging in high-risk activities and can be morally disengaged (Bellis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that understanding psychosocial processes is the best way to explain unethical behavior among youth Lee et al, 2022). Various forms of youth interpersonal violence, such as victimization and delinquency, have been linked in studies with lower levels of self-control, resilience and different forms of domestic violence (Akpunne et al, 2020;Jones & Pierce, 2021). Adults who are exposed to domestic violence during their childhood are susceptible to engaging in high-risk activities and can be morally disengaged (Bellis, 2014).…”
Section: Introductionmentioning
confidence: 99%